Cardiovascular complications in a patient with Systemic Lupus Erythematosus, according to the pathophysiology of the disease: literature review - Cruz-Ossa, Natalia (2023)
Introduction: Systemic lupus erythematosus (SLE) is an autoimmune disease that can affect any system of the individual's body, developing a wide variety of clinical manifestations. Each patient varies in the presentation of the disease, delaying their diagnosis and management. The main cause of death in these patients is caused by cardiovascular complications, such as stroke and myocardial infarction. Objective: To identify the cardiovascular complications that can develop in patients with SLE, according to the pathophysiology of the disease. Method: A systematic search of the literature in Medline was carried out using the guidelines of the PRISMA Declaration for the selection of published studies, using the terms "Systemic lupus erythematosus" and "cardiovascular disease". Results: Taking into account the 30 publications obtained in the systematic search of the literature, 24 demonstrated the presence of a relationship between SLE and the development of cardiovascular complications. These complications include atherosclerosis, stroke, peripheral vascular disease, myocarditis, among others, the most common being stroke, myocardial infarction, and atherosclerosis. Conclusions: SLE is a pathology involving several body systems, most commonly presenting with constitutional, mucocutaneous and musculoskeletal symptoms. However, it is essential to recognize the cardiovascular complications that can develop from this inflammatory pathology as well. This way, it is possible to reach an opportune diagnosis and provide better management, to reduce mortality from this cause.